Effect of 405 nm Diode Laser with Varying Irradiation Time on BHK-21 Fibroblast Viability - Kun Ismiyatin; Leidy Herlin Rumbiak; Widya Saraswati; Sri Kunarti; Anuj Bhardwaj (Universitas Airlangga, 2019)
Background: Laser is a device that emits light through a process of optical amplification based on the stimulated emission of electromagnetic radiation; it can be used for surgery, detoxification, bio stimulation and antibacterial. However, lasers have Biphasic Dose Response (BDR), which is bio stimulation and bio inhibition. To determine if 405 nm laser diode is biocompatible, viability test is necessary before these lasers can be labeled as viable to use in dental therapy. Aim: To prove the variation of radiation time of the 405 nm laser diode radiation can cause bio stimulation and bio inhibition response that affects the viability of BHK-21 fibroblast cells. Method: Viability test was carried out using BHK-21 fibroblast cells which were inserted into 96-well microplate, then radiated with 405 nm laser diode with varying irradiation time of 30s, 60s, 120s, 240s and 480s. After radiation, the cells are then incubated for 24h. Cytotoxicity was observed using MTT assay and ELISA reader. Data was analyzed using the Kolmogorov-Smirnov test, Levene Test, Welch ANOVA, and Tukey HSD. Results: BHK-21 fibroblast cells radiated with 405 nm laser diode with radiation time of 30s, 60s, 120s, and 240s have the same viability as the control cell, while at 480 seconds the viability exceeds that of the control cell. Conclusion: 405 nm laser diode with radiation times of 30s, 60s, 120s, and 240s do not affect the viability of BHK-21 fibroblast cells. Meanwhile, 480s irradiation time of 405 nm laser diode causes bio stimulation response that increases the viability of BHK-21 fibroblast cells.